2022
DOI: 10.1038/s42003-021-02985-3
|View full text |Cite
|
Sign up to set email alerts
|

Trans cohort metabolic reprogramming towards glutaminolysis in long-term successfully treated HIV-infection

Abstract: Despite successful combination antiretroviral therapy (cART), persistent low-grade immune activation together with inflammation and toxic antiretroviral drugs can lead to long-lasting metabolic flexibility and adaptation in people living with HIV (PLWH). Our study investigated alterations in the plasma metabolic profiles by comparing PLWH on long-term cART(>5 years) and matched HIV-negative controls (HC) in two cohorts from low- and middle-income countries (LMIC), Cameroon, and India, respectively, to under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
(56 reference statements)
0
15
0
Order By: Relevance
“…A synergistic effect of different factors (i.e., an increased pro-inflammatory state induced by HIV, age-related pathophysiological changes, exposure to early-generation ART, and the use of ART with the active agent NNRTIs), which perturb the functions within the biological system of HIV-infected, could play a part in the alterations of the identified biological mechanisms in the phenotype PLWH with MetS. A recent large study from India and Cameroon also reported alterations in glutaminolysis as a common factor in PLWH in long-term cART ( 32 ). Alterations in the lipid homeostasis, as well as glutaminolysis in PLWH, need clinical or dietary interventions as they might drive accelerated aging in PLWH with MetS.…”
Section: Discussionmentioning
confidence: 99%
“…A synergistic effect of different factors (i.e., an increased pro-inflammatory state induced by HIV, age-related pathophysiological changes, exposure to early-generation ART, and the use of ART with the active agent NNRTIs), which perturb the functions within the biological system of HIV-infected, could play a part in the alterations of the identified biological mechanisms in the phenotype PLWH with MetS. A recent large study from India and Cameroon also reported alterations in glutaminolysis as a common factor in PLWH in long-term cART ( 32 ). Alterations in the lipid homeostasis, as well as glutaminolysis in PLWH, need clinical or dietary interventions as they might drive accelerated aging in PLWH with MetS.…”
Section: Discussionmentioning
confidence: 99%
“…The co-expression network analysis was performed as described previously ( Arif et al, 2021 ) and adapted in viral diseases ( Appelberg et al, 2020 ; Mikaeloff et al, 2022 ). Networks were built by computing pairwise Spearman rank correlations between all genes after removal of non-expressed (row median FPKM <1) or lowly variant (row variance <0.1) genes and analyzed in igraph for those displaying statistically significant (adjusted p < 0.001) positive correlations.…”
Section: Methodsmentioning
confidence: 99%
“…Untargeted metabolomics provides a comprehensive and systematic response to the metabolome, while targeted metabolomics is more focused on the quantitation of specific metabolites. In practical applications, both approaches are often used in combination to complement each other (Asim et al , 2020 ; Thomas et al , 2020 ; Jia et al , 2022 ; Mikaeloff et al , 2022 ; Yelamanchi et al , 2022 ). For example, in the study of Xiao et al ( 2021 ), the combination of untargeted and targeted metabolomics revealed that disturbed metabolic pathways associated with hyperinflammation in severe COVID‐19 could be targeted with metabolic interventions as a possible approach to inhibit SARS‐CoV‐2‐induced cytokine release syndrome.…”
Section: Targeted and Untargeted Metabolomics For Immunology Researchmentioning
confidence: 99%